(3cJGH GdbVGAs - (3eQJVi Hf eMeO Cejf GdORahdj GdCfUGQj, J (B1281 (3g` s
(3ChdgG (B:s
(3cGf edcg XGgQjkG aEfg dh Med GdTQGA Ydi Pdc de jYde Gdedc GdeWdb s
(3BNQgG (B:s
(3ceG dh de jcf dgG hdO CUdkG hjchf JQcg GdGHf dCHjg s
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B201s
(3JHUQGJ GdCUd (B:s
(3GdfSNI fGbUI GdChd s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3CUhd Gdabgs